Healing with Code: AI's Transformative Impact on Healthcare and Homoeopathy. - Yaligouda, Jineshwar Annasaheb; Yaligouda, Padmraj Jineshwar (Homoeopathic Heritage, 2026)
The integration of Artificial Intelligence (AI) in healthcare and homoeopathy is revolutionizing patient care, diagnosis, and treatment. This article explores AI's transformative impact on healthcare and homoeopathy, highlighting its applications, benefits, and challenges. AI powered predictive analytics, medical imaging, and chatbots are enhancing diagnostic accuracy, personalizing treatment plans, and streamlining clinical workflows. In homoeopathy, AI aids remedy selection, patient profiling and research. While data privacy and regulatory frameworks remain concerns, AI's potential to improve health outcomes and effi- ciency is undeniable. This article discusses double edge AI's synergy with healthcare and homoeopathy, shaping a future where precision, compassion, and innovation converge. The integration of AI with homoeopathic medicine allows practitioners to make faster and more informed decisions, ultimately benefiting patients who need personalized care. From symptom analysis to remedy suggestions, AI powered homoeopathy is taking personalized treatment to the next level.